An effective CFD approach for marine-vehicle maneuvering simulation based on the hybrid reference frames method. (15th November 2015) - Wu, Xiaocui; Wang, Yiwei; Huang, Chenguang; Hu, Zhiqiang; Yi, Ruiwen
Abstract: The computational efficiency of CFD on maneuverability simulation poses a great difficulty resulting in its restricted applications. A hybrid reference frames method is established that combines the rotating reference frame method and an added momentum source method. The computational domain is separated into two parts under the rotating reference frame and the inertial frame respectively. A single mesh is needed for all conditions of a testing model such as different rotating arm radius, pitch angles and drift angles. The validation is carried out based on the numerical simulations on the flow fields around the SUBOFF models including sterns and full appended models. Results show that the stability derivatives of the yawing moment and yawing force agree well with the experimental data. Using a dimensional analysis method, the influences of the rotating arm radius and linear velocity are investigated. The similarity is maintained when the radius is constant, and the rotating effect performs strongly when the radius is small. The effects of pitch angle and drift angle are also discussed when the linear velocity is fixed with the fully appended SUBOFF model. Highlights: Flow past a freely suspended cylinder is experimentally investigated. Different response categories are observed with variable flow velocity.. The vortex wake mode is significantly affected by the trajectory of the cylinder. An intermittent translation and oscillation phenomenon is observed.